Analyzing Grammatical Interference on EFL Students' Indonesian-English Translation - Fauziah Fujiyanti; Elis Homsini Maolida; Jauhar Helmie (Siliwangi University, 2022)
Learning a foreign language is sometimes difficult since the target language has different elements and rules compared to the native language. When the students apply those elements and rules, it often leads to errors. In this case, when a student is learning a foreign language, the students’ native language will have an impact on the production of the language being learned which is called language interference. This study aims at investigating the types of interference and which type of interference appears more in EFL students’ Indonesian-English translation text. This study involved twenty students of the first grade in a senior high school in Cianjur. It is descriptive qualitative research with the data taken from students’ translation text that were analyzed by using error analysis to point out and describe the interference. The findings show that all participants of this research made errors in their translation text. In this case, four types of error found in the text, those were omission, addition, misformation, and disordering. The differences in the structures between two languages and different proficiency levels of students in target language led the students commited different error types in four error categories. The result of the analysis also shows that there were 413 errors found in the students’ translation text which consisted of 121 omissions (29,29%), 96 additions (22,27%), 156 misformation (38%), and 44 disordering errors (11%). From those frequencies, the most frequent error was misformation. Misformation indicates the use of an incorrect form of a certain linguistic in the target language utterance.Keywords: Language Interference, Indonesian-English Translation, Translation Text, Error Analysis, Classification of Error